Ensuring Failure?: The Impact of Class on Girls in Swedish Secure Care. Issue 2 (1st June 2021) - Vogel, Maria A.
Abstract: Historically, the regulation of girls through institutionalization has been guided by bourgeois norms of femininity, including virtue, domesticity, and motherhood. Using a Foucauldian perspective on the production of subjects in Swedish secure care, I investigate whether or not middle-class norms of femininity, centered today around self-regulation, still guide the regulation of working-class girls. By analyzing data from an ethnographic study, I show that even though secure care is repressive, it is also permeated with the aim of producing self-regulating subjects corresponding with discourses on ideal girlhood. However, since working-class girls are rarely made intelligible within such discourses, thereby making the position of self-regulatory subject inaccessible, the care system leaves them to shoulder the responsibility for resolving a situation that is shaped by structures beyond their control.